Philosophical and Ethical Insights in Halal Animal Slaughter Training: A Case Study of the Batu Bara Malay Community - Faishal, Muhammad (Jurnal Pemikiran Islam, 2024)
The Batu Bara Malay community has expressed concerns about the halalness of animal slaughter practices, particularly involving chickens and ducks, in the local animal market. In response, the Indonesian Ulema Council of Tanjung Tiram Sub-district (MUI TANBARSU) organized training to ensure compliance with Islamic standards. This study aims to analyze the philosophical and ethical values embedded in the training program. Employing a qualitative case study approach, data were gathered through field observations, in-depth interviews, and documentation. The findings revealed that the training incorporated educational elements emphasizing Islamic teachings, ethical standards, and technical aspects of halal slaughtering. The practical sessions further reinforced participants’ understanding of these values. The research concludes that the training program not only addresses community doubts about halal slaughter but also promotes a deeper integration of religious philosophy, ethics, and technical standards into slaughtering practices, contributing to consumer trust and the preservation of Islamic principles in the Batu Bara Malay community.